On the line [videorecording (DVD)] - Walter, Harriet; Pierreson, Royce; Lucie, Victoria (Trinity Home Entertainment, 2024)
Alderney, 1964. Agnes works alone as a switchboard operator in the telephone exchange. When she receives a strange call from Shirley, suffering from dementia and unable to clearly articulate what is happening around her, there's a blood curdling scream down the line, and the call cuts. Worried, Agnes sets about gleaning information from other callers in an attempt to piece together what's happened. Things soon take a turn for the worse when she realises everything is not as it seems.